The Implementation of One-Week-One-Article Program in a Reading Class: A Reflective Practice - Yudi Rahmatullah (University of Muhammadiyah Prof. DR. HAMKA, 2017)
This article presents my reflections on the implementation of one-week-one-article program. Fifty-three students participated in this program. Every week they presented the article they had read. I found that the majority of students actively participated in this program, showing seriousness in understanding the content of the article, the pronunciation of difficult words, and the flow of the presentation. This program at least promoted three aspects: students’ motivation, cooperative learning, and their critical thinking. Even though this program was conducted for university students, it is likely to be working with students of junior and senior secondary school with some modification.